An appraisal of the contributions of herbalism to primary health care delivery in south west Nigeria (2010)
Herbalism contributes significantly to the primary health care delivery system in the southwest Nigeria through sale and administration of different herbal medicinal preparations which are available in a number of ways like tinctures, herbal wine and elixirs, tisanes, decoctions, macerates, topical, poultices, whole herb consumption, syrup, extracts, inhalation, local rings, incision and rubbing, charm belt, and other charm apparels. Medicines may be hawked by the ambulatory vendors (apothecary) or patients consulting practitioners. Charges are relatively cheap, consultation is prompt and the medicines are reportedly efficacious. Non-exclusion of anybody from patronizing and being organized around people’s needs and expectations, which are two of the key elements of WHO to achieve the ultimate goal of primary health care of better health for all are affectively entrenched in the practice. We adopted and employed basic scientific method, anthropological training skills and study approaches in Humanities to elicit our findings. Government support is highly solicited